Quantitative assessment of the vascularity of the skeletally immature patella: a cadaveric study using MRI. (2021) - Gadinsky, Naomi E.; Lin, Kenneth M.; Klinger, Craig E.; Dyke, Jonathan P.; Kleeblad, Laura J.; Shea, Kevin G.; Helfet, David L; Rodeo, Scott A.; Green, Daniel W.; Lazaro, Lionel E.
Abstract: Purpose: While predominant blood supply to the adult patella enters inferomedially, little is known about skeletally immature patellar perfusion. Improved knowledge of immature patella vascularity can further understanding of osteochondritis dissecans, dorsal defects of the patella and bipartite patella, and help ensure safe surgical approaches. We hypothesized that the immature patella would exhibit more uniform blood flow. The study purpose was to quantify immature patella regional perfusion in comparison with adults. Methods: Ten cadaveric knees were utilized (five immature, five mature). The superficial femoral artery was cannulated proximally. Signal enhancement increases were compared from pre- to post-contrast MRI to assess relative arterial contributions to patella regions (quadrants, anterior/posterior, superior/inferior, medial/lateral, and outer/inner). Results: Quantitative-MRI analysis revealed similar distribution of enhancement between the immature and mature patella. The inferior pole exhibited significantly higher arterial contribution versus superior pole in both immature and mature groups (p = 0.009; both groups), while the inferomedial quadrant had the highest arterial contribution of all quadrants in both groups. The superolateral quadrant demonstrated the lowest arterial contribution in the immature group and second lowest in the adult group. The patella outer periphery had significantly greater arterial contribution than the inner central region in both immature (p = 0.009) and mature (p = 0.009) groups. Conclusion: Distribution of arterial contributions between the immature and mature patella was similar. Our results highlight the importance of inferior and inferomedial blood supply in both immature and mature patellas. These findings have implications for paediatric and adult patients; surgical damage to inferior patellar vessels should be avoided to prevent associated complications.